1987
DOI: 10.1002/zaac.19875510827
|View full text |Cite
|
Sign up to set email alerts
|

Massenspektroskopische Analyse der Verdampfung von AlF3

Abstract: Die Verdampfung von AlF3 wurde massenspektrometrisch unter Verwendung zweier verschiedener Meßanordnungen analysiert. Es konnte auf diese Weise nachgewiesen werden, daß HFAlF3‐Gaskomplexe bei der Verdampfung auftreten. Neben dem monomeren Komplex HAlF4 ist die Bildung von weiteren Gaskomplexen wahrscheinlich.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Direct experimental information is available for only two of the vapor phase complexes considered in this paper: the HF−AlF 3 molecule has been detected by dynamic thermal gas analysis coupled with mass spectrometry; the HCl−AlCl 3 complex has been evidenced by mass spectrometry too. , Quantum chemical ab initio calculations have shown that all HX−AlX 3 complexes (X = F, Cl) can be described as weak electron pair donor−acceptor adducts with a long and weak intermolecular halogen bridge. The HF and HCl molecules primarily act as electron donors rather than proton donors in these complexes. The Cl atom in HCl is a weaker Lewis base than the F atom in HF. , …”
Section: Experimental Challenge and Dilemmamentioning
confidence: 99%
See 1 more Smart Citation
“…Direct experimental information is available for only two of the vapor phase complexes considered in this paper: the HF−AlF 3 molecule has been detected by dynamic thermal gas analysis coupled with mass spectrometry; the HCl−AlCl 3 complex has been evidenced by mass spectrometry too. , Quantum chemical ab initio calculations have shown that all HX−AlX 3 complexes (X = F, Cl) can be described as weak electron pair donor−acceptor adducts with a long and weak intermolecular halogen bridge. The HF and HCl molecules primarily act as electron donors rather than proton donors in these complexes. The Cl atom in HCl is a weaker Lewis base than the F atom in HF. , …”
Section: Experimental Challenge and Dilemmamentioning
confidence: 99%
“…The complex nature of thermal phase transitions in aluminum fluoride hydrates , gave strong evidence for the formation of AlF 3 −OH - or AlF 3 −H 2 O complexes. (The existence of HF−AlF 3 and 2HF−AlF 3 was directly proven during such processes. , ) Thermally induced processes such as water loss, hydrolysis occurring after the main water content was given up, and the formation of the highly reactive species HF accompanied by a complex chemical and physical reorganization of the solid cause the appearance of a spontaneous catalytic active β-AlF 3 phase above 450 °C. Menz et al assumed that the intermediate formation of solid and gaseous aluminum fluoride oxides plays a crucial role for the reorganization processes taking place in the solid. F/OH - exchange processes could be proven during dehydration processes .…”
Section: Experimental Challenge and Dilemmamentioning
confidence: 99%